Balloon dilatation of pacemaker induced stenosis of the superior vena cava. Issue 4 (April 1991) - Grace, A A; Sutters, M; Schofield, P M
Abstract : A 53 year old woman with symptomatic pacemaker associated superior vena cava syndrome was treated successfully with balloon angioplasty. She was well six months after the procedure.